2013
DOI: 10.1016/j.firesaf.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

On the extrapolation of CFD results for smoke and heat control in reduced-scale set-ups to full scale: Atrium configuration

Abstract: It is common practice to use reduced-scale experiments to develop formulae for the design of smoke and heat exhaust ventilation systems. Implicitly, up-scaling of results is assumed justified. A similar approach can be adopted with numerical simulations, i.e. a reduced-scale setup can be up-scaled to compare results to full-scale observations. However, both in numerical simulations and in experiments, scaling must be done in a proper way. The classical method for up-scaling results obtained in fire related exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…21 The applicability of FDS for tunnel fire research has been effectively verified. 22,23 24 It can be found that scholars have mainly studied the temperature characteristics of tunnel fires in the conditions of weak plumes. Therefore, a simulation of a small-scale tunnel is established based on FDS to carry out a numerical simulation study of tunnel fire with strong fire plume conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The applicability of FDS for tunnel fire research has been effectively verified. 22,23 24 It can be found that scholars have mainly studied the temperature characteristics of tunnel fires in the conditions of weak plumes. Therefore, a simulation of a small-scale tunnel is established based on FDS to carry out a numerical simulation study of tunnel fire with strong fire plume conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Tilley achieved the retention of the Reynolds number and Froude number by changing the ambient air viscosity coefficient and gravity in FDS, and obtained good similarity results in the reduced‐scale model. At the same time, they also pointed out that if the Reynolds number is insufficient, the retention of the Froude number only would cause great experimental error 24 …”
Section: Introductionmentioning
confidence: 99%
“…Vauquelin et al [29] discussed some scaling laws and concluded that when the Boussinesq approximation cannot be assumed, a density distortion between full scale and reduced scale is not compatible with full similitude. Tilley [30] studied the application of scaling laws in an atrium configuration and the results showed that preserving the Froude number alone is not sufficient when the flow becomes weakly turbulent.…”
mentioning
confidence: 99%
“…It is noted that even the flows for fires with heat release rates of 5.6 kW and 11.2 kW were in a turbulent region, which satisfied the requirements of Froude scaling laws, significant errors in the temperature rises, smoke concentrations, as well as velocities were observed. Tilley [30] pointed out that preserving the Froude number alone is not sufficient when the flow becomes weakly turbulent. For natural ventilation in tunnels, the velocities of the upper zone and lower zone are large enough for fully turbulent flow.…”
mentioning
confidence: 99%
“…此外, 模型 实验中气流在高于临界雷诺数的条件下流动(即雷诺 数处于自模区), 气流流动与雷诺数无关, 因此, 不 必保证模型和原型的雷诺数相同. 最终, 阿基米德数 成为描述气流流型的关键参数 [12] .…”
unclassified